The Effect of Role-Playing Methods on the Development of Children's Social Behavior in Group B at Al-Fiqihiyah Kindergarten in Palu City - Fitrianti Yatinde; Durrotunnisa Durrotunnisa; Amrullah Amrullah; Nurhayati Nurhayati (FKIP - Universitas Riau, 2026)
This study aims to determine the effect of role-playing methods on the development of children's social behavior in Group B of Al-Fiqihiyah Kindergarten in Palu City. Social behavior is an important skill that needs to be developed from an early age, including caring, cooperation, and mutual assistance. This study used a quantitative approach with a one-group pretest-posttest design, involving 15 children as research subjects. Data collection techniques included observation, interviews, and documentation, while data analysis was performed statistically using a t-test through the SPSS program. The results showed a significant increase in children's social behavior after being given treatment in the form of role-playing methods. The pretest average score of 4.93 increased to 8.13 on the posttest. In addition, the Not Yet Developed (BB) category, which previously dominated, decreased dramatically to 0% after the treatment, while the Developing as Expected (BSH) and Developing Very Well (BSB) categories increased significantly. The t-test showed a Sig. (2-tailed) value of 0.000 < 0.05, which means H0 is rejected and H1 is accepted, so it can be concluded that the role-playing method has a significant effect on children's social behavior. Thus, the role-playing method can be used as an effective learning strategy in developing the social aspects of early childhood.